Factors Associated with Accreditation Status of Private Clinics in Pekanbaru City in 2024 - Iin Sriderfi Sitompul; Jasrida Yunita; Yessi Harnani; Ahmad Hanafi; Kiswanto (LPPM Universitas Harapan Bangsa, 2024)
Primary clinics play a crucial role in improving public health through healthcare services, disease prevention, and education. However, the challenges in accreditation preparation include the staff's lack of technical understanding in completing applications, limited facilities such as computers, and insufficient support from clinic leadership and monitoring from the Health Office. This study aims to analyze factors related to the accreditation status of primary clinics in Pekanbaru City in 2024. The population consisted of 198 people, with a sample size of 198 respondents. Data analysis was conducted using univariate, bivariate, and multivariate analyse. There is a relationship between activity standardization (p= 0.000), completeness of clinic facilities (p= 0.000), activity coordination (p= 0.016), leadership support (p= 0.013) and attitude (p= 0.005) with the accreditation status of the Pratama Clinic. There is no relationship between knowledge factors (p= 0.596), competence (p= 0.319), work team support (p= 0.237), ease of access to information technology systems (p= 0.074), motivation (p= 0.826) and support from the Health Office (p= 0.367) with the accreditation status of the Pratama Clinic. The most dominant variable related to the accreditation status of the Pratama Clinic in Pekanbaru City in 2024 is the activity standardization variable (POR= 11.572). Suggestion: The Pratama Clinic needs to routinely evaluate and update operational procedures to ensure compliance with national accreditation standards. In addition, the establishment of an internal monitoring system and additional training on ASPAK applications, DFO, and managerial skills are essential to maintain compliance and improve operational effectiveness.